Anemia at Discharge in Elderly Trauma Patients is Not Associated with Six-Month Mortality. Issue 7 (July 2019) - Ong, Adrian W.; Muller, Alison; Sigal, Adam; Fernandez, Forrest
Few studies have evaluated outcomes in geriatric trauma patients discharged with anemia. Our hypothesis was that anemia at discharge was not associated with six-month mortality. A 22-month retrospective study of trauma patients ≥ 65 years was conducted from 2015 to 2016. The end point was six-month mortality. The degree of anemia at admission (admission hemoglobin [AHb]) and discharge (discharge hemoglobin [DHb]) was categorized as follows based on hemoglobin (Hb) (g/dL): I (>10), II (>9 and ≤10), III (>8 and ≤9), and IV (≤8). Univariate analysis and multivariate analysis were performed to determine the association of AHb and DHb with the end point. Nine hundred forty-nine patients were analyzed (median age, 82 years). Six-month mortality was 11 per cent. Mortality was associated with AHb by univariate analysis (I:10% [84/831]; II: 13% [9/67]; III: 22% [7/32]; and IV: 26% [5/19]) ( P = 0.003). DHb was not associated with mortality (I:11% [65/613]; II: 12% [21/183]; III: 10% [12/116]; and IV: 18% [7/39]) ( P = 0.37). Logistic regression found that AHb category IV, age, and chronic kidney disease were independently associated with the end point. In geriatric patients, the severity of anemia at admission and not at discharge predicted six-month mortality. Discharging patients with an Hb of ≤8 g/dL was not adversely associated with mortality.